Homelessness, citizenship, and identity : the uncanniness of late modernity - Arnold, Kathleen R., 1966- (SUNY series in national identities., 2004)
"In this study, Kathleen R. Arnold explores homelessness in terms of the globalization of the economy, national identity, and citizenship. She argues that domestic homelessness and conditions of statelessness, such as refugees, exiles, and poor immigrants, are defined and addressed in similar ways by the political sphere, in such a manner that each of these groups are subjected to policies that perpetuate their exclusion. Drawing on such authors as Freud, Marx, Foucault, Derrida, Levinas, and Agamben, Arnold argues for a radical politics of homelessness based on extending hospitality and the toleration of difference."--Jacket